Identity and Economic Incentives - Kwabena Donkor; Lorenz Goette; Maximilian W. Müller; Eugen Dimant; Michael Kurschilgen (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines how beliefs and preferences drive identity-conforming consumption or investments. We introduce a theory that explains how identity distorts individuals' beliefs about potential outcomes and imposes psychic costs on benefiting from identity-incongruent sources. We substantiate our theoretical foundation through two lab-infield experiments on soccer betting in Kenya and the UK, where participants either had established affiliations with the teams involved or assumed a neutral stance. The results indicate that soccer fans have overoptimistic beliefs about match outcomes that align with their identity and bet significantly higher amounts on those than on outcomes of comparable games where they are neutral. After accounting for individuals' beliefs and risk preferences, our structural estimates reveal that participants undervalue gains from identity-incongruent assets by 9% to 27%. Our counterfactual simulations imply that identity-specific beliefs account for 30% to 44% of the investment differences between neutral observers and supporters, with the remainder being due to identity preferences.
Keywords: D91; G41; Z10; 330; identity; investments; beliefs